(NpOWESTI I RASSKAZY (B/ s (N~ASTX (B2s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1978)
(Nw TOM WHODQT IZWESTNYE PROIZWEDENIQ l(B. (Nn(B. (NtOLSTOGO(B, (NSOZDANNYE IM W (B1872-1906 (NGG(B., (NKAK (B"(NkREJCEROWA SONATA(B", "(NdXQWOL(B", "(NoTEC sERGIJ(B" (NI DR(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs